STRATEGI WALI KELAS DALAM MENGATASI KESULITAN BELAJAR SISWA (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Abstract Research on homeroom teacher strategies in overcoming class II students' learning difficulties at SDI Al-Furqon uses a qualitative research type with a descriptive approach. The results of this study are: First, the homeroom teacher's strategy in overcoming learning difficulties is to provide motivation to students, provide training, when there are only a few students who do not understand, the homeroom teacher explains again using a personal approach or can be called one by one, and provides special time during recess to students who have learning difficulties, namely reading. Second, the inhibiting and supporting factors, the supporting factors are from the students' parents, within the students themselves where students are very enthusiastic in carrying out reading guidance during recess. Inhibiting factors are students who do not attend school, lack of adequate facilities, and friends outside of school or the surrounding environment. Third, the influence of the role of the guardian is parents who encourage by motivating students at home while the homeroom teacher controls all students' understanding at school. So the homeroom teacher has a bigger role. Keywords:Strategies, homeroom teacher, learning difficulties